2010
DOI: 10.2298/mpns1010624z
|View full text |Cite
|
Sign up to set email alerts
|

Activity of superoxide dismutase and catalase and content of malondialdehyde in seminal plasma of infertile patients

Abstract: The reactive oxygen species, the highly reactive metabolites of oxygen, play a crucial role in both the normal function and the metabolism of sperm cells. Oxygen radicals achieve their physiological effects in the cells only if there is a proper balance between their production and degradation. In case of radicals' production exceeding the antioxidant capacity of the semen, there is an oxidative damage of the membrane lipids and proteins as well as the DNA damage followed by the fragmentation and decondensatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 27 publications
4
18
0
Order By: Relevance
“…These results were biologically reasonable and highlighted the central role of CAT in detoxification of ROS and its protection of spermatozoa integrity, in agreement with and supported those reported by Khosrowbeygi et al [2004] who showed that an altered CAT state can have a significant role in the etiology of impaired sperm function. Our results also supported those of Zelen et al [2010], in which they showed fertile donors had significantly higher CAT activities in seminal plasma than infertile men. Our results also supported those of Ramya et al [2011].…”
Section: Resultssupporting
confidence: 90%
“…These results were biologically reasonable and highlighted the central role of CAT in detoxification of ROS and its protection of spermatozoa integrity, in agreement with and supported those reported by Khosrowbeygi et al [2004] who showed that an altered CAT state can have a significant role in the etiology of impaired sperm function. Our results also supported those of Zelen et al [2010], in which they showed fertile donors had significantly higher CAT activities in seminal plasma than infertile men. Our results also supported those of Ramya et al [2011].…”
Section: Resultssupporting
confidence: 90%
“…Evidence from the literature demonstrates that oxidative stress has harmful effects on spermatogenesis (Asadi, Bahmani, Kheradmand, & Rafieian‐Kopaei, ; Guerriero, Trocchia, Abdel‐Gawad, & Ciarcia, ; Tremellen, ). Free radicals have the ability to directly damage sperm DNA by attacking the purine and pyrimidine bases and the deoxyribose backbone (Zelen, Mitrović, & Jurisic‐Skevin, ). They can initiate apoptosis within the spermatozoa, leading to caspase‐mediated enzymatic degradation of the DNA modifying susceptible molecules including lipids and proteins (Tremellen, ).…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, the scavenging action of albumin has also been emphasized, reflecting the ability of this protein to act both as a sacrificial antioxidant and as a docking site for lipid peroxides clipped out of the plasma membrane by phospholipase A2 (Armstrong et al, 1998; Twigg et al, 1998). Additional small‐molecular‐mass scavengers such as vitamin E are also present in seminal plasma, as are antioxidant enzymes, particularly glutathione peroxidase and superoxide dismutase, as well as some catalase‐like activity, particularly in the rabbit (Foote and Hare, 2000; Zelen et al, 2010; Moretti et al, 2011). Incidentally, the latter observation explains why addition of hydrogen peroxide to rabbit semen has no discernable effect on sperm motility in seminal plasma (Wales et al, 1959).…”
Section: The Role Of Ros In Sperm Cell Biologymentioning
confidence: 99%